Enhancing European Security - Cuthbertson, Ian M. author. aut Link
XV, 223 p.
Keywords: Although the authors believe that the level of conventional and nuclear forces in Europe should and will be reduced, they do not consider that the military instrument will have lost all of its value in European political affairs. They still see a need to be prepared for tension and conflict.